Transactive energy management and system design for multi-energy networks - Zou, Yunyang (Nanyang Technological University, 2024)
A multi-energy system (MES), also referred to as a multi-energy network or an integrated energy system, has gained widespread recognition as a cost-efficient, environmentally-friendly, and reliable energy supply paradigm over recent decades. The classical energy management methods for MESs mainly focus on supply-side management to match energy demands. However, with the increasing integration of distributed energy resources (DERs) such as photovoltaic (PV), wind, and flexible loads, the intermittent nature of renewable generation and the uncertain behaviors of flexible consumers/prosumers have posed formidable challenges to the operation and management of MESs. To tackle these new challenges, the emerging concept of transactive energy offers promising solutions. Therefore, this thesis is devoted to the design of transactive energy system (TES), also known as transactive energy management, for MESs. This thesis first summarizes and analyzes the designs of state-of-the-art TESs. Subsequently, a series of new transactive energy management methods, including both centralized and peer-to-peer (P2P) methods, are developed to meet diverse application scenarios. Finally, the ancillary service markets necessary for supporting P2P transactive energy management are also designed.